Pengaruh Komunikasi terhadap Kepuasan Kerja Karyawan Industri Jasa Keuangan di Bandung - Sitti Nurrachmah (KOMVERSAL, 2021)
ABSTRACT Communication satisfaction is one form of communication interaction results that can form a theoretical approach to understanding the field of communication. This study aims to determine the effect of communication on job satisfaction. The research method uses quantitative data analysis and hypothesis testing using multiple regression statistics. Communication satisfaction is composed of various dimensions that form the concept of communication satisfaction. In a scientific context, the impact of communication satisfaction has become an important topic in the literature considering its impact on employee attitudes and behavior. This study tries to examine the relationship between the three dimensions of communication satisfaction, namely personal feedback, relations with supervisors, and the communication climate with one of the most popular organizational outputs, namely job satisfaction. The results showed that the dimensions of personal feedback and relations with supervisors had a positive and significant effect on job satisfaction. The dimension of communication climate has no significant effect on job satisfaction. The practical impact, for companies, can improve and improve the quality of communication. Keywords: job satisfaction, communication satisfaction, personal feedback, relation with supervisor, communication climate. ABSTRAK Kepuasan komunikasi merupakan salah satu bentuk hasil interaksi komunikasi yang dapat membentuk pendekatan teoritis untuk memahami bidang komunikasi. Studi ini bertujuan mengetahui pengaruh komunikasi terhadap kepuasan kerja. Metode penelitian menggunakan kuantitatif dengan analisis data dan pengujian hipotesis menggunakan statistic regresi berganda. Kepuasan komunikasi tersusun atas berbagai dimensi yang membentuk konsep kepuasan komunikasi. Pada konteks ilmiah, dampak kepuasan komunikasi telah menjadi topik penting dalam literatur mengingat dampaknya terhadap sikap maupun perilaku karyawan. Studi ini mencoba mengkaji keterkaitan antara ketiga dimensi kepuasan komunikasi yaitu personal feedback, relation with supervisor, dan communication climate dengan salah satu keluaran organisasi yang paling populer yaitu kepuasan kerja. Hasil penelitian menunjukkan bahwa dimensi personal feedback dan relation with supervisor mempunyai pengaruh positif dan signifikan terhadap kepuasan kerja. Adapun dimensi communication climate tidak berpengaruh signifikan terhadap kepuasan kerja. Dampak secara praktis, bagi perusahaan bisa meningkatkan dan memperbaiki kualitas komunikasi.